Intravaginal Brachytherapy in FIGO Stage I Low-Risk Endometrial Cancer: A Controlled Randomized Study. Issue 5 (1st July 2009) - Sorbe, Bengt; NordstrÖM, Britta; MÄEnpÄÄ, Johanna; Kuhelj, Janez; Kuhelj, Dimitrij; Okkan, Sait; Delaloye, Jean-Francois; Frankendal, B.
Abstract : The purpose of the study was to compare postoperative vaginal irradiation with surgery alone in low-risk International Federation of Gynecology and Obstetrics (FIGO) stage IA-IB endometrial carcinoma. The study was a prospective, randomized trial of 645 evaluable low-risk endometrial carcinoma patients from 6 European gynecologic cancer centers. All tumors were in FIGO stage IA-IB, of endometrioid histological type, and FIGO grade 1-2. High-dose-rate afterloading equipments (iridium [Ir] 192 or cobalt [co] 60) were used at 5 centers, and low-dose-rate (LDR) afterloading equipment (cesium [Cs] 137) at 1 center. Perspex vaginal applicators or ovoids were normally used, and the dose was specified at 5 mm from the surface of the applicator. Three to 6 fractions (3.0-8.0 Gy) were given, and the overall treatment time was 4 to 15 days. A total of 319 patients were treated with surgery plus vaginal irradiation (treatment group), and 326 patients with surgery alone (control group). Twenty-six recurrences (4.0%) were recorded in the complete series. The locoregional recurrence rate was 2.6%, whereas distant metastases occurred in 1.4%. The rate of vaginal recurrences was 1.2% in the treatment group versus 3.1% in the control group. The difference was not statistically significant ( P = 0.114). Side effects were few and mild (grade 1-2). Dysuria, frequency, and incontinence were slightly more common after vaginal irradiation (2.8% vs 0.6%, respectively). Late intestinal problems were few and similar in the 2 groups. The conclusions were that the impact of postoperative brachytherapy on even the locoregional recurrence rate seems to be limited in patients with low-risk endometrial carcinoma. The overall recurrence rate and survival were similar in the 2 groups.